2001
DOI: 10.1097/00001756-200110290-00043
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of NPY Y2 receptor subtype in the control of the spontaneous NO/GnRH release at the rat median eminence

Abstract: The role of nitric oxide (NO) from vascular endothelium in the control of GnRH release at the median eminence (ME) level is well established. Interactions between NPY receptor/endothelium/nitric oxide are clearly demonstrated. While several studies implicate NPY Y1 receptor in the control of GnRH/LH at the time of the preovulatory LH surge, our results also demonstrate the importance of NPY Y2 receptor in the control of GnRH release via endothelial NO. We conclude that NPY may be one of the elements implicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…We suggest from our study that NPY may be a marker for null-cell adenomas. This conclusion is similar to that of Grouzmann et al [9] Our data showed that the NPY expression level in prolactinomas was obviously lower than that of other subtypes of pituitary adenomas. As a neuroendocrine peptide, NPY can be considered to be a signal amplifier that plays different roles in modulating physiological functions.…”
Section: Discussionsupporting
confidence: 93%
“…We suggest from our study that NPY may be a marker for null-cell adenomas. This conclusion is similar to that of Grouzmann et al [9] Our data showed that the NPY expression level in prolactinomas was obviously lower than that of other subtypes of pituitary adenomas. As a neuroendocrine peptide, NPY can be considered to be a signal amplifier that plays different roles in modulating physiological functions.…”
Section: Discussionsupporting
confidence: 93%
“…NO plays an important role in the female reproductive system and in the release of Gonadotropin-releasing hormone (GnRH) (Knauf et al. 2001). GnRH may stimulate the pituitary gland to release follicle-stimulating hormone and luteinizing hormone, which together, can promote the growth and development of ovarian follicles.…”
Section: Discussionmentioning
confidence: 99%